Multidisciplinary analysis including neotectonic mapping, morphotectonic indices, applied geophysics and remote sensing techniques for studying recently recognized active faults in Northwestern Peloponnese (Greece) - Mavroulis, S.; Dilalos, S.; Alexopoulos, J.D.; Vassilakis, Emm.; Lekkas, E. (2nd Scientific Meeting of the Tectonics Committee of the Geological Society of Greece, 2019)
A multidisciplinary analysis comprising neotectonic mapping, morphotectonic indices, applied geophysics and remote sensing techniques was applied in the area affected by the 2008 NW Peloponnese (Western Greece) in order to map the recently-recognized E-W striking Pineios River normal fault zone with a high degree of accuracy, and to better understand its contribution to the evolution of the ancient region of Elis during Holocene time. Quantitative constraints on deformation caused by the faulting were applied through the application of morphometric and morphotectonic indices including drainage network asymmetry, longitudinal river profiles and valley floor slope changes, the river sinuosity index (SI) of modern channels as well as mountain front indices including mountain front sinuosity (Smf) and percentage of faceting along mountain front (F%). All of the aforementioned indicated that the Pineios fault zone is a highly active structure.